(untitled) (American Journal of Islam and Society, 2014)
Few are as qualified as Imam Feisal Abdul Rauf to articulate a vision for American Muslims. He has been involved with several major institutionbuilding projects to address the concerns of American Muslims; his wife, Daisy Khan, has also participated in some of these projects. Since 1983, he has served as imam of New York City’s al-Farah Mosque and thus is rather familiar with the achievements, struggles, and diversity of the American- Muslim experience. His involvement with one of this community’s most formative post-9/11 undertakings, the Cordoba House Project (also known as Park 51 and the Ground Zero Mosque), attracted national and international attention. Several other American Muslims have written about the community. For example, James Yee’s For God and Country (2005), Sumbul Ali-Karamali’s The Muslims Next Door (2008), and Asma Nomani’s Standing Alone in Mecca (2006) have experienced modest mainstream success. Mucahit Bilici’s Finding Mecca in America (2012) is a notable, although a more academic, work. Imam Rauf’s book belongs to the first genre. Aimed at a general audience, it provides a good understanding of such issues as jihad and gender relations in Islam, the Shari‘ah, and American-Muslim identity formation. Book Reviews 127 The author’s key idea is that American Muslims are on their way to creating a unique identity, one that is true to the spirit of Islam and also fits into American cultural norms. If fully realized, this identity would have three major potential benefits: making the United States more tolerant and just, healing the wounds between it and the broader Muslim world, and inspiring Muslims everywhere to reclaim Islam from the extremists. According to Rauf, this identity can only be fully realized if Muslims have a good understanding of Islam, uphold American laws, and engage in the country’s ongoing multi-faith projects ...